Dynamics of training and acute exercise-induced shifts in muscular glucose transporter (GLUT) 4, 8, and 12 expression in locomotion versus posture muscles in healthy horses - Vidal Moreno de Vega, Carmen; Lemmens, Diete; de Meeûs d’Argenteuil, Constance; Boshuizen, Berit; de Maré, Lorie; Leybaert, Luc; Goethals, Klara; de Oliveira, Jean Eduardo; Hosotani, Guilherme; Deforce, Dieter; Van Nieuwerburgh, Filip; Devisscher, Lindsey; et al. (Frontiers in Physiology, 2023)
Important changes in glucose transporter (GLUT) expression should be expected if the glucose influx plays a pivotal role in fuelling or connecting metabolic pathways that are upregulated in responseanswer to exercise. We aimedThe aim was to assess GLUT4, 8, and 12 dynamics in response to training and acute exercise.Methods: Sixteen untrained Standardbred mares (3-4y) performed an incremental SET at the start and end of 8 weeks harness training. M. pectoralis (PM) and Mm. vastus lateralis (VL) muscle biopsies were taken before and after each SET, allowing for comparing rest and acute samples in untrained (UT) and trained (T) condition using Western Blot for GLUT quantification and Image Pro v.10 for Blot analysis. Data were normalized against GAPDH. Statistical analysis was performed using GraphPad.Basal GLUT-levels of PM versus VL were analysed with the Wilcoxon matched-pairs signed rank test.The effect of acute exercise or training was assessed using the Friedman test with a post-hoc Dunn's.Results: Basal GLUT4 and GLUT12 protein expression were significantly higher in the VL compared to the PM (PGLUT4 = 0.031 and PGLUT12 = 0.002). Training had no effect on basal GLUT4 expression, neither in the VL (P > 0.9999), nor the PM (P > 0.9999). However, acute exercise in trained condition significantly decreased GLUT4 expression in the VL (P = 0.0148). Neither training nor acute exercise significantly changed total GLUT8 protein expression. Training significantly decreased total GLUT12 protein expression in rest biopsies, only visible in the VL (P = 0.0359). This decrease was even more prominent in the VL after acute exercise in trained condition (PVL = 0.0025).The important changes seen in GLUT12 expression downregulation, both in answer response to training and acute exercise in the horse, the downregulation of GLUT4 expression after acute exercise in trained condition and the lack of differential shifts in GLUT8 expression in any of the studied conditions, questions the importance of glucose as substrate to fuel training and exercise in healthy horses. These findings encourage to further explore alternative fuels for their involvement in equine muscular energetics.